Arsitektur Kurikulum Program Syarqi di Markaz Arabiyah: Pembelajaran Komunikatif, Tugas-Proyek, dan Imersi dalam Kerangka IMTĀʾ dan CEFR - Mitrajati, Kenyo; Titis Trilaksito; Miqdarul Khoir Syarofit (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
Purpose – This study examines the curriculum architecture of the Syarqi Program at Markaz Arabiyah, Pare, Kediri, by tracing the interconnection of objectives, content, strategies, media, evaluation, and learning environment within the IMTĀʾ framework and the language of CEFR learning outcomes. Design/methods – This research employed a qualitative case study based on document analysis. The data corpus included curriculum documents, subject structures, formulations of Basic Competencies and achievement indicators, evaluation schemes, descriptions of supporting programs, and visual artifacts as markers of practical context. The analysis was conducted through deductive coding based on IMTĀʾ components and the four language skills, then deepened inductively to read task types, language products, and competency trajectories. Findings – The documents show that the four language skills constitute the core of the curriculum and are strengthened through role play, storytelling, creative projects, discourse exercises, portfolios, and a dormitory-based immersion ecosystem. The mapping of Basic Competencies and achievement indicators reveals a trajectory from mastery of basic language elements toward communicative tasks that demand coherence, structural accuracy, and situational response. At the design level, the Syarqi Program indicates proximity to the al-Kifāyah spectrum and, in certain tasks, features moving toward at-Tamayyuz. However, the claim of CEFR A2-B1 proficiency still requires stable performance evidence and assessment procedures so that it does not remain merely a language of outcomes.